Machine Learning Approaches for Enhancing Customer Retention and Sales Forecasting in the Biopharmaceutical Industry: A Case Study - Xiaowen Ma; Jiayi Wang; Xin Ni; Jiatu Shi (International Journal of Engineering and Management Research, 2024)
This study explores the evolving role of artificial intelligence (AI) in accelerating drug discovery and development in the biopharmaceutical industry. We research the integration of AI technologies, including machine learning algorithms, deep learning, and natural language processing, with traditional experimental techniques. Research focuses on four main areas: target identification and validation, identification and optimization, reproducible medicine, and precision medicine. Our findings show that an AI-driven approach has improved the efficiency and accuracy of the various stages of drug discovery, reducing the time and costs associated with bringing new treatments to action. Business. We analyze the synergistic effects of combining AI predictions with biological knowledge models, highlighting the potential for modeling and optimization. This study also examines the critical role of data quality and the importance of data models in training AI models. Additionally, we address issues of AI model interpretation and regulatory decision-making around AI-driven drug discovery. Ethical implications are discussed, including data privacy and equality for AI-driven healthcare innovations. Our research shows the potential of AI in changing the drug discovery process while highlighting the need for improved roles and technology in the biopharmaceutical sector.